Boxer's Knuckle. Issue 1 (22nd November 2021) - Watté, Nina; Walschot, Luc; Vanhoenacker, Filip
Teaching Point: Persistent metacarpophalangeal joint pain after clenched-fist trauma with an unremarkable conventional radiography justifies further examination with dynamic ultrasound for detecting extensor hood injuries.